Nilai Perusahaan pada Industri Consumer Goods Non-cyclical: Perspektif Teori Agensi - Fachrunnisa, Zidni Husnia; Zulia Putri, Anandita; Pramudiati, Ningrum; Laraswati, Aisya (Universitas PGRI Yogyakarta, 2025)
This study aims to empirically test whether family ownership, profitability, and dividend policy are factors that influence firm value in the non-cyclical consumer sector. Agency theory is used as the underlying theory in this study. This quantitative study uses secondary data derived from the annual reports of non-cyclical consumer companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sampling method used was purposive sampling with certain criteria. Data analysis used multiple linear regression with SPSS statistical tools. The results of this study empirically prove that family ownership and profitability have a positive effect on firm value. Meanwhile, dividend policy has no effect on firm value. Firm value can increase with increasing family ownership and increasing profitability. A limitation of this study is that the three independent variables used only have a small effect on the dependent variable. Suggestions for further research include adding more years of research and other independent variables to increase the influence on the dependent variable